2016
DOI: 10.1111/jopr.12483
|View full text |Cite
|
Sign up to set email alerts
|

Technique to Match Gingival Shade when Using Pink Ceramics for Anterior Fixed Implant Prostheses

Abstract: Use of pink gingival ceramics can reduce the necessity for extensive surgical procedures attempting to restore missing soft and hard tissues in the maxillary esthetic zone. Selecting the appropriate shade for pink porcelain poses a challenge, especially when the patient presents with a high smile line. This paper describes a simple and effective technique to facilitate shade selection for gingival ceramics to match the patient's existing gingival shade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…However, they can be a disadvantage with high smile line patients as it is mostly indicated for moderate and low smile patients. [ 8 ] The reason is transition line exposure of gingiva and artificial pink substitute’s visibility during smile. The precise location of this line in apical direction depends on a clinician’s ability to create crestal concavity at its border to harbor artificial gingival extension with a convex profile.…”
Section: Discussionmentioning
confidence: 99%
“…However, they can be a disadvantage with high smile line patients as it is mostly indicated for moderate and low smile patients. [ 8 ] The reason is transition line exposure of gingiva and artificial pink substitute’s visibility during smile. The precise location of this line in apical direction depends on a clinician’s ability to create crestal concavity at its border to harbor artificial gingival extension with a convex profile.…”
Section: Discussionmentioning
confidence: 99%
“…Gingival shade matching, often overlooked, plays an integral role in designing fixed prostheses for patients with high smile lines, and gingival defects, and in cases where the acrylic flange of removable dentures extends into the aesthetic zone [ 4 ]. A recent study showed that ethnicity and age had a significant impact on the color of the gingiva [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the soft tissue materials, gingival-colored pink porcelain stands out due to its superior aesthetics [10]. Pink porcelain has been shown to enhance aesthetics and is effective in masking negotiated surgical outcomes [11,12]. However, to achieve an ideal aesthetic outcome, the restorative material must reproduce the natural color of the tissues.…”
Section: Introductionmentioning
confidence: 99%